Elaboración de un video interactivo como objeto de aprendizaje sobre evaluación de la parálisis facial periférica. - Téllez García, Gina Fabiola; Campos Navarro, Luz Arcelia (Anales de Otorrinolaringología Mexicana, 2013)
BACKGROUND: The physician's role is to ensure a health care system, set in a culture of quality and patient safety. O ne of the issues where we consider there is difficulty in the quality of teaching-learning process is about the facial nerve. In response to this need, and after consulting with experts and review of current literature, we decided to create an interactive digital tool to the educational process for learning about the Facial Nerve. T he peripheral facial nerve disorders are more frequent, so it is important to distinguish from those of central origin, whose treatment differs from one another. In the medical residency, one of the educational problems is the limitation on the time devoted to study, what we consider important to conduct a learning object that could exploit the information technology and communication, it can be done asynchronously and thereby facilitate access to educational and enforcement of academic programs. OBJECTIVE: To develop an interactive video as a learning object on the assessment of peripheral facial paralysis. MATERIAL AND METHOD: A video with the use of multimedia, which shows information related to anatomical and physiological bases of the facial nerve and evaluation processes used in specific clinical scales most widely applicable and Sunny Brook House Brackmann. We carried out the selection of adult patients with peripheral facial palsy, recordings were made of how the evaluation of the consent. T he videos were sent for evaluation by a round of five experts, who evaluated quality, when expressed in the same tried and evaluated as the level of infection with the two scales. T he answer should be 5 and if this was feasible the use of scales. Adjustments were performed. H e took out the video and submitted for evaluation using evaluation scale learning object. RESULTS: There was an interactive video, with the use of multimedia with pictures and videos taken from patients with peripheral facial paralysis. T here was the round of experts was based on the Reply 5 of 5 in all, appropriate adjustments were made. T he video assessment using the scale of learning objects was rated optimal. CONCLUSIONS: We believe that interactive video can be used as objects of instruction for undergraduate and postgraduate doctors and to help better use of resources and time for optimal learning.